Algebra 1: Common Core (15th Edition)

Published by Prentice Hall
ISBN 10: 0133281140
ISBN 13: 978-0-13328-114-9

Chapter 10 - Radical Expressions and Equations - 10-3 Operations With Radical Expressions - Practice and Problem-Solving Exercises - Page 629: 27


The answer is $-6$.

Work Step by Step

We can simplify the expression as follows: $=(2+\sqrt10)(2-\sqrt10)$ $=2^{2}-\sqrt10^{2}$ (Since $a^{2}-b^{2}=(a+b)(a-b)$) $=4-10$ $=-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.